2015
DOI: 10.1007/s00726-015-1988-z
|View full text |Cite
|
Sign up to set email alerts
|

Taurine supplementation ameliorates glucose homeostasis, prevents insulin and glucagon hypersecretion, and controls β, α, and δ-cell masses in genetic obese mice

Abstract: Taurine (Tau) regulates β-cell function and glucose homeostasis under normal and diabetic conditions. Here, we assessed the effects of Tau supplementation upon glucose homeostasis and the morphophysiology of endocrine pancreas, in leptin-deficient obese (ob) mice. From weaning until 90-day-old, C57Bl/6 and ob mice received, or not, 5% Tau in drinking water (C, CT, ob and obT). Obese mice were hyperglycemic, glucose intolerant, insulin resistant, and exhibited higher hepatic glucose output. Tau supplementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Surprisingly, taurine treatment abolished the daily pattern of glucose-stimulated insulin secretion in isolated islets from HFD-fed mice. The reason is not known, but it could be possible that taurine could modulate important metabolic genes involved in the regulation of insulin secretion and beta-cell mass, as shown in previous studies with taurine supplementation in obese animals4142.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, taurine treatment abolished the daily pattern of glucose-stimulated insulin secretion in isolated islets from HFD-fed mice. The reason is not known, but it could be possible that taurine could modulate important metabolic genes involved in the regulation of insulin secretion and beta-cell mass, as shown in previous studies with taurine supplementation in obese animals4142.…”
Section: Discussionmentioning
confidence: 99%
“…During each enteral-hepatic cycle, about 95% of the liver-derived bile salts are reabsorbed to the liver. ASBT apical sodium-dependent bile salt/acid transporter (in ileal enterocytes), BA bile acids (unconjugated), BSEP bile salt export pump, CBA conjugated bile acids, Gly glycine, GlyT glycine transporters, M3 multidrug resistance protein-3, MBSL microbial bile salt hydrolases, NTCP Na + -taurocholate cotransporting polypeptide, OATP organic anion transporting polypeptide family, OSTα/β organic solute transporter subunit α/β, PD passive diffusion, Tau taurine, TauT taurine transporters taurine can ameliorate structural abnormalities of the pancreas (Santos-Silva et al 2015), while improving insulin production by pancreatic β-cells (Nakatsuru et al 2018) and whole-body insulin sensitivity in subjects with hyperglycemia (Sarkar et al 2017). This role of taurine in diabetic patients are highly significant, because they have a 25% lower concentration of taurine in plasma than normal subjects (Sak et al 2019) and that the number of type-2 diabetic patients is increasing globally (Willet et al 2019).…”
Section: Health Benefits Of Taurine Supplementationmentioning
confidence: 99%
“…Also, it can induce apoptosis and inhibit the proliferation of HCC HepG2 cells [26] and induced apoptosis of human colon cancer [27]. Tau also could prevent the development of ameliorates glycemia, the action of insulin, and dyslipidemia in type 2 diabetes mellitus (T2DM) [28]. Another study showed that post-treatment supplemention of taurine is recommended for T2DM [29].…”
Section: Introductionmentioning
confidence: 99%